ORBITAL REMOTE SENSING FOR EVAPOTRANSPIRATION MODELING: THEORETICAL OVERVIEW AND APPLICATIONS IN CLOUD COMPUTING - de Oliveira Ferreira Silva, César; Jandreice Magnoni , Pedro Henrique; Lilla Manzione, Rodrigo (Revista Brasileira de Engenharia de Biossistemas, 2021)
The objective of this review article was compiling the theoretical and technological aspects of remote sensing-based evapotranspiration (ET) modeling. We surveyed the thermohydrological concepts that support the ET phenomenon, such as soil energy fluxes ("thermo") and hydrological balance. We also present the main variants of the ET concept. Models based on remote sensing are focused on the actual ET. We survey the most disseminated models applied to satellite imagery (to be implemented by the researcher) and present their assumptions, limitations and opportunities.Finally, we surveyed ready-made actual ET databases (available on Google Earth Engine - GEE), and for these we developed interactive panels for data extraction. With these panels it is possible to easily extract actual ET time series and perform subsequent calibrations with field data.